1997
DOI: 10.1063/1.363915
|View full text |Cite
|
Sign up to set email alerts
|

Field emission properties of diode devices based on amorphic diamond-Si heterojunctions

Abstract: Microscopic and macroscopic field emission properties of amorphic diamond films on n- and p-type silicon substrates were studied by combined scanning tunneling microscopy/spectroscopy and integral field emission I–V measurements. Microscopic scanning tunneling spectroscopy showed that amorphic diamond films on n-Si have lower threshold voltage and higher emission current than amorphic diamond films on p-Si. The observed rectification characteristics suggest that amorphic diamond on n-Si is an ideal forward-bia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…The field emission of electrons from diamond-like carbon (DLC) films deposited by different methods has been reported [1][2][3][4][5][6][7][8][9][10]. Two forms of DLC films, amorphous carbon (a-C) [1][2][3][4][5][6][7][8] and hydrogenated amorphous carbon (a-C:H) [9,10], have been studied. DLC films consist of sp 2 coordinated clusters embedded in an sp 3 coordinated carbon matrix [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The field emission of electrons from diamond-like carbon (DLC) films deposited by different methods has been reported [1][2][3][4][5][6][7][8][9][10]. Two forms of DLC films, amorphous carbon (a-C) [1][2][3][4][5][6][7][8] and hydrogenated amorphous carbon (a-C:H) [9,10], have been studied. DLC films consist of sp 2 coordinated clusters embedded in an sp 3 coordinated carbon matrix [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The volume fraction of sp 3 bonds is increased by the hydrogenation of films [11,12], and a-C:H films emit electrons at a lower field than a-C films [8,9]. It has been reported that the electron emission from DLC depends on several factors, such as the low work function of sp 3 clusters, field enhancement at emission sites by the formation of a nano-columnar structure of carbon films and doping and/or defects in sp 3 clusters [1][2][3][4][5][6][7][8][9][10]. However, the emission current from DLC emitters has been limited to several tenths of a micro-ampere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most interesting characteristics of amorphous carbon films is the variability of their electronic, optical and mechanical properties. They are governed by the relative concentration of the three different carbon bond configurations, sp 1 , sp 2 and sp 3 , that can exist simultaneously in a carbon film. During preparation, it is possible to vary this ratio, thereby tailoring the material for various important technological applications.…”
Section: Introductionmentioning
confidence: 99%
“…During preparation, it is possible to vary this ratio, thereby tailoring the material for various important technological applications. The characteristics of the heterojunctions made by depositing amorphous carbon on crystalline silicon (c-Si) are a subject of increasing interest because of their potential application in a variety of electronic devices [1][2][3][4]. A fundamental problem is that of understanding the way in which the band gaps of the constituent semiconductors are aligned when the junction is formed.…”
Section: Introductionmentioning
confidence: 99%